Reduced Severity in Patients With HIV-Associated Disseminated Histoplasmosis With Deep Lymphadenopathies: A Trench War Remains Within the Lymph Nodes? - Nacher, Mathieu; Alsibai, Kinan Drak; Adenis, Antoine; Blaizot, Romain; Abboud, Philippe; Demar, Magalie; Djossou, Félix; Epelboin, Loïc; Misslin, Caroline; Ntab, Balthazar; Valdes, Audrey; Couppié, Pierre (Frontiers in Cellular and Infection Microbiology, 2021)
Background Disseminated histoplasmosis is a major killer of patients with advanced HIV. It is proteiform and often hard to diagnose in the absence of diagnostic tests. We aimed to describe disseminated histoplasmosis with lymphadenopathies in French Guiana and to compare survival and severity of those patients to patients without lymphadenopathies. Methods A retrospective cohort study was performed on data records collected between January 1, 1981 and October 1, 2014. Results Among 349 cases of disseminated histoplasmosis 168 (48.3%) had superficial lymphadenopathies and 133(38.1%) had deep lymphadenopathies. The median LDH concentration, ferritin concentration, TGO concentration, and WHO performance status were lower among patients with deep lymphadenopathies than those without deep lymphadenopathies. There was a significant decrease in the risk of early death (<1 month) among those with deep lymphadenopathies relative to those without (OR=0.26 (95%CI=0.10–0.60), P=0.0006) and in the overall risk of death (OR=0.33 (95%CI=0.20-0.55), P<0.0001). These associations remained strongly significant after adjusting for time period, CD4 counts, age, delay between beginning of symptoms and hospital admission, antifungal and antiretroviral treatment. Conclusions The present data show that in patients with advanced HIV and disseminated histoplasmosis, the presence of deep lymphadenopathies is associated with fewer markers of severity and a lower risk of death. To our knowledge it is the first study to show this. The presence of deep lymphadenopathies is hypothesized to reflect the patient’s partially effective defense against H. capsulatum.